PERBANDINGAN PENERAPAN METODE PEMBELAJARAN ROLE PLAYING DENGAN PEMBELAJARAN KONVENSIONAL TERHADAP HASIL BELAJAR KIMIA SISWA SMA NEGERI 1 LORE UTARA - Masrita, Masrita; Gonggo, Siang Tandi; Sabang, Sri Mulyani (Jurnal Akademika Kimia, 2013)
Research dealing with role-play Learning and conventional learning methods, have been conducted. The main reason for this research was that chemical bond was one of the difficult but fundamental materials to be mastered by the students at grade X. The purpose of this research was to investigate the students’ achievement on the topic of chemical bond at SMA Negeri 1 North Lore. One way of increasing their achievement was by using role-play method. In order to make their learning understandable, not boring, and easy to grasp, the researcher applied an interesting method called role-play. The population of this research was the tenth grade students of SMA Negeri 1 North Lore in the academic year 2012/2013. The sample was 32 students of grade XA as the experimental group (role-play) and 32 students of grade XC as the control group (conventional learning). The data were collected through the test on chemical bond. Based on the analysis, it is found that the average score of the experimental group was 20.65 with deviation standard of 2.413 and of the control group was 15.06 with deviation standard of 2.975. The hypothesis testing was that the t-counted value was 12.75 and the t-table value was 1.67 with the significant value (α) of 0.05. The results showed that there was a significant difference in the students’ achievement dealing with the topic of chemical bond through the application of role-play learning method and conventional learning method at grade X at SMA Negeri 1 North Lore in the Academic Year 2012/2013.